2019
DOI: 10.1093/braincomms/fcz016
|View full text |Cite
|
Sign up to set email alerts
|

To be or not to be pink(1): contradictory findings in an animal model for Parkinson’s disease

Abstract: The PTEN-induced putative kinase 1 knockout rat (Pink1−/−) is marketed as an established model for Parkinson’s disease, characterized by development of motor deficits and progressive degeneration of half the dopaminergic neurons in the substantia nigra pars compacta by 8 months of age. In this study, we address our concerns about the reproducibility of the Pink1−/− rat model. We evaluated behavioural function, number of substantia nigra dopaminergic neurons and extracellular striatal dopamine concentrations by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
28
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 21 publications
(32 reference statements)
4
28
2
Order By: Relevance
“…The Pink1 −/− rat model does have limitations, including less dopamine depletion than is seen in humans, hindlimb issues which may be an unknown consequence of the genetic mutation, and less behavioural robustness than the mouse model. As clearly described in de Haas et al 1 , there have been studies by several groups, including ours, that have failed to replicate findings of consistent limb motor changes by 8 months of age with severity of nigrostriatal dopamine depletion. We agree with de Haas et al 1 that there is a lack of reproducibility of the original 25–50% reduction reported by Dave et al 11 Additional explanation for the discrepancies, not addressed in the paper, may include experimental controls such as light cycle, age and use of rat breeding lines, as well as social enrichment variables, especially with frequent behavioural testing.…”
mentioning
confidence: 41%
See 4 more Smart Citations
“…The Pink1 −/− rat model does have limitations, including less dopamine depletion than is seen in humans, hindlimb issues which may be an unknown consequence of the genetic mutation, and less behavioural robustness than the mouse model. As clearly described in de Haas et al 1 , there have been studies by several groups, including ours, that have failed to replicate findings of consistent limb motor changes by 8 months of age with severity of nigrostriatal dopamine depletion. We agree with de Haas et al 1 that there is a lack of reproducibility of the original 25–50% reduction reported by Dave et al 11 Additional explanation for the discrepancies, not addressed in the paper, may include experimental controls such as light cycle, age and use of rat breeding lines, as well as social enrichment variables, especially with frequent behavioural testing.…”
mentioning
confidence: 41%
“…As clearly described in de Haas et al 1 , there have been studies by several groups, including ours, that have failed to replicate findings of consistent limb motor changes by 8 months of age with severity of nigrostriatal dopamine depletion. We agree with de Haas et al 1 that there is a lack of reproducibility of the original 25–50% reduction reported by Dave et al 11 Additional explanation for the discrepancies, not addressed in the paper, may include experimental controls such as light cycle, age and use of rat breeding lines, as well as social enrichment variables, especially with frequent behavioural testing. In fact, we found that when we do not assay multiple behaviours every 1–2 months, behavioural deficits and brain neurochemistry is different than in animals that receive consistent conspecific and experimenter/handler interactions.…”
mentioning
confidence: 41%
See 3 more Smart Citations